2021
DOI: 10.5937/jpmnt9-34130
|View full text |Cite
|
Sign up to set email alerts
|

Credit Rating Agencies and Their Effects: An Analysis on Balkan Countries

Abstract: The financial structure in the world has become more complex with the increase in global capital movements. For this reason, credit rating agencies have emerged as an important component of the financial structure. Standard and Poors, Moody's and Fitch are the three most important companies in this market. The grades given by these institutions highly affect the economic situation of the countries. In this study, information is given about credit rating agencies and it is aimed to measure the effect of the poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In addition, the credit ratings given by international credit rating agencies such as S&P, Fitch and Moody's are also influential on country economies. Yıldırım, Üre and Karaköy (2021), in their study on the subject, concluded that the scores given by credit rating agencies have an effect on real growth. According to the study, since the ratings given by these institutions are a guide for foreign investors, low ratings affect growth negatively by causing less foreign investment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the credit ratings given by international credit rating agencies such as S&P, Fitch and Moody's are also influential on country economies. Yıldırım, Üre and Karaköy (2021), in their study on the subject, concluded that the scores given by credit rating agencies have an effect on real growth. According to the study, since the ratings given by these institutions are a guide for foreign investors, low ratings affect growth negatively by causing less foreign investment.…”
Section: Introductionmentioning
confidence: 99%